ADHD and time perception: Findings and treatments - Weissenberger, Simon; Klicperová-Baker, Martina; Vňuková, Martina; Raboch, Jiří; Ptáček, Radek (Activitas Nervosa Superior (2007), 2019)
This mini review aims to explore the intricate connection between ADHD and time perception along with some new findings on new treatments to manage ADHD symptoms. The topic of time perception is addressed from a variety of perspectives and with an understanding that although differences in time perception are not listed among the primary symptoms of the disorder, they are of the utmost importance to understand the condition and possibly new treatment plans. We also review some of the new findings on ADHD and time perception, and look at the usefulness of certain psychometric tools like the Zimbardo Time Perspective Inventory recent research into educational video games and apps for managing the disorder.
Keywords: Zimbardo Time Perspective Inventory; hyperkinetická porucha; Attention Deficit Disorder with Hyperactivity; lidé; hra a hračky; vnímání času; Time Perception; Play and Playthings; Humans